Comparison of costs, mechanical strength, and quality between traditional and reinforced adobe - Christian Johnson Carrasco-Ahen; Josualdo Carlos Villar Quiroz (Epistemus)
In Peru, traditional constructions with adobe blocks have shown structural vulnerabilities during seismic events. This study comparatively analyzed the costs, mechanical strength, and quality of traditional versus reinforced adobe using a quantitative approach and a non-experimental design. The results indicate that reinforced adobe increases costs by 4.7% to 11.3% compared to traditional adobe. Adobe with 200 g of quicklime achieved the highest mechanical strength: 20.44 kg/cm² in compression, 2.56 kg/cm² in flexion, and 0.32 kg/cm² in mortar tensile strength. Additionally, adobe with 10% by weight of eucalyptus bark fiber obtained an excellent quality index (90%). It is concluded that, although traditional adobe is more economical, its low mechanical strength and insufficient quality index make it unsuitable for construction according to NTE.080. Therefore, reinforced adobe is positioned as a move viable alternative.